The Effect of Geometric Parameters on the Strength of Stone Columns - Saxena, S.; Roy, L. B. (Engineering, Technology & Applied Science Research, 2022)
Abstract-Many geotechnical sites are unsuitable for construction due to their low bearing capacity. In the present study, stone column technique has been analyzed for the ground improvement of soft clayey soil. The change in bearing capacity of stone columns with variation in static parameters has been estimated using Indian Standard Code 15284 (IS Code) - 2003, Bouassida’s method (1994), and Afshar’s and Ghazavi’s method (2014). From the analytical solution of the expression by the IS Code method for bearing capacity of the stone column, it is found that with the increase in diameter of the column, the bearing capacity of the stone column increases. Comparison of the results from the three methods has been conducted and it was found that values obtained from IS Code are very close to those obtained by the other two analytical methods. Also, the critical interpretation of the results shows that the IS Code gives safer design values for a wide range of the static parameters. The results of the IS Code were compared with the experimental findings to evaluate the ability of the method to design the actual load carrying capacity of the stone column.